A3. Oxidative stress in maternal serum as endothelial dysfunction marker in preeclampsia, an electron paramagnetic resonance (EPR) pilot study. (12th August 2016) - Mannaerts, D.; Faes, E.; Gielis, J.; Briedé, J.; Cos, P.; Van Craenenbroeck, E.; Gyselaers, W.; Cornette, J.; Spaanderman, M.; Jacquemyn, Y.
Abstract: Aims : Oxidative stress is crucial in the pathophysiology of preeclampsia. Reactive oxygen species (ROS) like the superoxide radical O2–, are produced by the ischemic placenta, causing systemic inflammation and endothelial dysfunction. EPR uses microwave radiation and a high magnetic field and is the most direct and reliable method to detect free radicals. We explored the feasibility of determining O2– concentration in maternal serum and compared pre-eclamptic and uncomplicated pregnancies. Methods : In this study a CMH (1–hydroxyl-3-methoxycarbonyl-2, 2, 5, 5-tetramethylpyrrolidine) spin trap stabilizing free O2-radicals for EPR detection, has been used. Twenty-four patients were included of which 12 pre-eclamptic pregnancies and 12 uncomplicated pregnancies. Results : EPR successfully detects O2– concentration in maternal serum. Results are presented inFigure 1 . Since there was an overt difference ( p = 0.007) between patients with HELLP syndrome versus pre-eclamptic patients with only hypertension and proteinuria, these patients were observed as a distinct group. A significant difference between uncomplicated and pre-eclamptic pregnancies ( p = 0.005) was observed. Discussion : We hypothesize that an increased protective scavenger system for ROS is activated in pre-eclampsia. In case of further decompensation as in HELLP syndrome, this system collapses resulting in increased vascular endothelial damage.